Advanced DC-DC Power Converters and Switching Converters - Musumeci, Salvatore (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Nowadays, power electronics is an enabling technology in the energy development scenario. Furthermore, power electronics is strictly linked with several fields of technological growth, such as consumer electronics, IT and communications, electrical networks, utilities, industrial drives and robotics, and transportation and automotive sectors. Moreover, the widespread use of power electronics enables cost savings and minimization of losses in several technology applications required for sustainable economic growth. The topologies of DC-DC power converters and switching converters are under continuous development and deserve special attention to highlight the advantages and disadvantages for use increasingly oriented towards green and sustainable development. DC-DC converter topologies are developed in consideration of higher efficiency, reliable control switching strategies, and fault-tolerant configurations. Several types of switching converter topologies are involved in isolated DC-DC converter and nonisolated DC-DC converter solutions operating in hard-switching and soft-switching conditions. Switching converters have applications in a broad range of areas in both low and high power densities. The articles presented in the Special Issue titled "Advanced DC-DC Power Converters and Switching Converters" consolidate the work on the investigation of the switching converter topology considering the technological advances offered by innovative wide-bandgap devices and performance optimization methods in control strategies used.